Undergraduate Nursing Students' Engagement and Associated Factors in Classroom Learning. - Masih, Younas; Rubab, Huma (Creative Nursing, 2025)
Higher education institutions are under pressure to improve the quality of education. Student engagement (SE) is among the critical indicators of quality education. Numerous studies demonstrated the engagement of nursing students in their learning environment. However, there is limited evidence on nursing students' engagement levels across academic years and post-pandemic restrictions. This study aimed to determine undergraduate nursing students' classroom engagement levels and associated factors across academic years. An analytical cross-sectional survey was conducted in Islamabad, Pakistan. Students enrolled in a Bachelor of Nursing Sciences program (n = 276) participated in this survey. Data were collected using a 40-item Student Engagement Questionnaire. Descriptive and inferential statistics were used for data analysis. Most undergraduate nursing students reported high (47.8%) or moderate (36.6%) levels of engagement. Higher engagement levels were reported in the self-directed learning and adaptability domains and moderate levels in student–teacher and student–student relationships. There was a difference across academic years regarding critical thinking and student health related. Grade point averages and cumulative grade point averages were unrelated to SE. Although most participants reported a high level of SE, the number of moderate-level achievers was significant. Therefore, the findings can be valuable for nursing educators and educational institutions to design effective strategies to improve the conduciveness of the teaching and learning environment and student engagement.